Pengaruh Pemberian VCO (VIRGIN COCONUT OIL) Terhadap Stabilitas Salep Ekstrak Etil asetat Daun Seligi (Phyllanthus buxifolius Muell. Arg) The Influence Of Giving Effect VCO (VIRGIN COCONUT OIL) To Stability Of Aethyl acetate Extract Ointment Of Seligi - Siwi Hastuti - Poltekes Bhakti Mulia Sukoharjo (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2017)
Abstract: Seligi (Phyllanthus buxifolius Muell. Arg) is an Indonesian native plant, which has been traditionally used as pain releaving drugs for treating sprains and rheumatism. Phytochemical screening was conducted to determine the chemical content in the aethyl acetate extract of the Seligi leaves. VCO is an oil derived from coconuts, used topically, serves to protect the skin from infection and free radicals and soften the skin.This research aims to determine the effect of variation levels against the physical stability of the ointment VCO aethyl acetate extract of seligi leaves.. First, the seligi leaf extracted by maceration method using aethyl acetate. Ointments are formulated into three levels VCO formula with a variation of 5%, 10%, and 20% use the seligi leaves extract concentration of aethyl acetate of 10% for each formula. Physical test include organoleptic test, homogeneity, pH, spread power, sticky power and protection power. Statistical analysis was performed with normality test with One-Sample Kolmogorov-Smirnov Test, homogeneity test with a Test of homogeneity, the next Variances One Way ANOVA test and Post Hoc Test. Differences VCO concentration in aethyl acetate extract ointment of seligi leaves effects for the physical characteristic material. The results of this research were obtained ointment preparation with an average pH 6 and homogeneous ointment material. The spread power and sticky power were obtained of normal result with significant value and homogeneus value.Keywords: Phyllanthus buxifolius, Seligi, VCO, ointments, rheumatism. Abstrak: Seligi (Phyllanthus buxifolius Muell. Arg) merupakan tanaman asli Indonesia yang sejak lama secara tradisional digunakan masyarakat sebagai obat nyeri pada sendi terkilir dan untuk mengobati rematik. Virgin coconut oil merupakan minyak yang berasal dari buah kelapa, digunakan secara topical, berfungsi untuk melindungi kulit dari infeksi dan radikal bebas serta dapat melembutkan kulit. Penelitian ini bertujuan untuk mengetahui pengaruh variasi kadar VCO terhadap stabilitas fisik salep ekstrak etil asetat daun seligi. Sebelumnya daun seligi diekstrak dengan metode maserasi menggunakan pelarut etil asetat. Salep diformulasikan menjadi tiga formula dengan variasi kadar VCO 5%, 10%, dan 20% menggunakan kadar ekstrak etil asetat daun seligi sebesar 10% untuk setiap formula. Uji sifat fisik meliputi organoleptis, homogenitas, pH, daya sebar, daya lekat, dan daya proteksi. Analisis statistik dilakukan dengan uji normalitas dengan One-Sample Kolmogorov-Smirnov Test, uji homogenitas dengan Test of Homogeneity of Variances selanjutnya dilakukan uji One WayANOVA dan Post Hoc Test. Perbedaan konsentrasi VCO pada sediaan salep ekstrak etil asetat daun seligi berpengaruh pada sifat fisik sediaan. Hasil dari penelitian ini diperoleh sediaan salep dengan pH rata-rata 6 dan salep homogen. Daya lekat dan daya sebar diperoleh hasil yang normal dan menunjukkan adanya perbedaan yang signifikan.Kata kunci :Phyllanthus buxifolius, Seligi, VCO, Salep.